The Effect of Village Assistance, Income, and Labor Skills on the Productivity of Village Communities (Case Study of Bumdesa Pamekasan Regency) - Yunianti, Dina; Idialis, Alifah Rokhmah (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze and examine the efficiency of productivity at the village level, which is influenced by village assistance, community income, and workforce skills in Pamekasan Regency. Although the region has a relatively high Human Development Index (HDI), it is not accompanied by an increase in per capita GRDP, indicating that productivity efficiency remains suboptimal. Survey findings show that most village communities in Pamekasan produce outputs below their optimal potential. This research offers a comprehensive approach by integrating three key variables village assistance, income, and labor skills into a single case study. A non-parametric deterministic frontier method was employed using Data Envelopment Analysis (DEA) with STATA 14. The results show that some Decision Making Units (DMUs) achieved full efficiency under constant returns to scale (CRS), while others remained inefficient under decreasing returns to scale (DRS). The study concludes that village assistance, community income, and workforce skills significantly influence the productivity efficiency of rural communities. Most villages affiliated with BUMDes have shown the ability to manage their resources efficiently to support community productivity.